Experienced teacher educators hunting assumptions to examine their pedagogy: An international collaborative study - Brandenburg, Robyn; Garbett, Dawn; Ovens, Alan Patrick; Thomas, Lynn (Frontiers in Education, 2023)
The research presented in this article focuses on an international collaboration conducted by four experienced teacher educators who used assumption identification and examination to advance pedagogical practice. It describes and examines how teacher educators deliberately undertook reflective practices to inform and enhance teaching. Four vignettes are described and analysed - Practica woes and Modelling practice - and examined using the simple, complicated, and complex teaching framework. The key outcomes include the impact and role of assumption definition, identification, and examination as powerful reflective tools. Researching practice in teacher education is an effective way to advance pedagogical knowledge and practice and a disposition of inquiry is necessary to enhance knowledge at all stages of teacher educator experience. This international collaboration highlights the importance of problematising teaching, continually inquiring into and interrogating practice and grasping the teachable moments.